Effects of treatment with antimicrobial agents on the human colonic microflora - Fatemeh Rafii; John B Sutherland; Carl E Cerniglia (Dove Medical Press, 2008)
Fatemeh Rafii, John B Sutherland, Carl E CernigliaDivision of Microbiology, National Center for Toxicological Research, FDA, Jefferson, AR, USAAbstract: Antimicrobial agents are the most valuable means available for treating bacterial infections. However, the administration of therapeutic doses of antimicrobial agents to patients is a leading cause of disturbance of the normal gastrointestinal microflora. This disturbance results in diminishing the natural defense mechanisms provided by the colonic microbial ecosystem, making the host vulnerable to infection by commensal microorganisms or nosocomial pathogens. In this minireview, the impacts of antimicrobials, individually and in combinations, on the human colonic microflora are discussed.Keywords: antibiotics, intestinal bacteria